Identification of a liver cirrhosis signature in plasma for predicting hepatocellular carcinoma risk in a population‐based cohort of hepatitis B carriers. Issue 1 (21st August 2012) - Liu, Chia‐Chi; Wang, Ya‐Hui; Chuang, Eric Y; Tsai, Mong‐Hsun; Chuang, Ya‐Hui; Lin, Chih‐Lin; Liu, Chun‐Jen; Hsiao, Bo‐Yu; Lin, Shi‐Ming; Liu, Li‐Yu; Yu, Ming‐Whei
Abstract Liver cirrhosis is a critical state in the natural course of hepatocellular carcinoma (HCC). We sought to investigate the potential of in‐depth proteomics to reveal plasma protein signatures that reflect common networks/pathways of liver cirrhosis, and to determine whether the cirrhosis‐related signature in plasma is linked to the development of HCC among hepatitis B virus (HBV) carriers. We first compared plasma protein profiles using a 174‐antibody microarray system between three groups of HBV carriers with different Child's grades of cirrhosis, which revealed a panel of 45 differentially expressed proteins with a high accuracy for discriminating Child's B/C. Ingenuity Pathway Analysis identified two main up‐regulated networks connecting the 45 proteins that were most enriched for genes in the pathway of hepatic stellate cell activation. A parsimonious subset of 11 pathway‐based proteins was then selected for quantification to correlate with HCC risk among 49 HCC cases and 50 controls in a nested case–control study within a 16‐yr follow‐up cohort of HBV carriers. A high risk score derived from a principal component analysis, which was used to extract the cluster structure of the 11 proteins, was associated with HCC (odds ratio = 4.83, 95% confidence interval: 1.26–18.56) even after adjustment for viral and clinical variables, implying the involvement of a pattern of coordinated proteins. Stepwise logistic regression on the 11 proteins revealed ICAM‐2 as an independent predictor for HCC. These findings may give further insight into the pathobiology of hepatocarcinogenesis, allow testing of the cirrhosis‐related plasma protein signature as a potential predictive biomarker for HCC. Copyright © 2012 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.